2020
DOI: 10.1155/2020/7453786
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenesis Regulation and Endocrine Disruptors: Emerging Insights in Obesity

Abstract: Endocrine disruptors (EDs) are defined as environmental pollutants capable of interfering with the functioning of the hormonal system. They are environmentally distributed as synthetic fertilizers, electronic waste, and several food additives that are part of the food chain. They can be considered as obesogenic compounds since they have the capacity to influence cellular events related to adipose tissue, altering lipid metabolism and adipogenesis processes. This review will present the latest scientific eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 85 publications
1
48
0
Order By: Relevance
“…A study of adults in NHANES showed that higher levels of metals in blood or urine were associated with higher body mass index (BMI) 28 . A review by González-Casanova et al suggests that the possible pathological pathway to this link is similar to the mechanism of endocrine disrupting chemicals 29 . Hematology-related outcomes, neurological, respiratory and psychiatric morbidities appeared to be associated with more than one dominant metal, which possibly has to do with their multi-factorial nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of adults in NHANES showed that higher levels of metals in blood or urine were associated with higher body mass index (BMI) 28 . A review by González-Casanova et al suggests that the possible pathological pathway to this link is similar to the mechanism of endocrine disrupting chemicals 29 . Hematology-related outcomes, neurological, respiratory and psychiatric morbidities appeared to be associated with more than one dominant metal, which possibly has to do with their multi-factorial nature.…”
Section: Discussionmentioning
confidence: 99%
“…A study of adults in NHANES showed that higher levels of metals in blood or urine were associated with higher body mass index (BMI) 28 . A review by González-Casanova et al suggests that the possible pathological pathway to this link is similar to the mechanism of endocrine disrupting chemicals 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes are functionally classified as endocrine-active and are sensitive to changes induced by endocrine disruptors, which have been termed “obesogens” [ 64 ]. These substances may trigger an increase in adiposity by altering the cellular development program in adipocytes, increasing triglyceride storage and interfering with the neuroendocrine control of hunger and satiety centers [ 65 , 66 ]. Some of the chemicals we typically encountered tend to cause changes in fat cell metabolism.…”
Section: Environment and Obesitymentioning
confidence: 99%
“…As described, many EDs have been established as MDCs and, as such, have adverse effects on metabolic health [15][16][17][18][19][20][21]. Suspected MDCs from compound classes that have been shown to interact with metabolism-related NRs, have effects on mitochondrial function, or cause adverse metabolic effects, e.g., by inhibiting key enzyme of glucose utilization, are prime candidates for EDCMET studies (Table 1).…”
Section: Edcmet Approachmentioning
confidence: 99%
“…Indeed, epidemiological data from humans and experimental data from rodents indicate that exposure to certain EDs, the so-called metabolism disrupting chemicals (MDCs), may predispose patients to different components of metabolic syndrome, T2D, and NAFLD (for reviews, see [15][16][17][18][19][20]). The main targets for MDCs are liver and adipose tissue, where they can provoke, e.g., adipogenesis and fat accumulation [21], insulin resistance [22], and changes in cholesterol and bile acid metabolism [18][19][20]. MDCs have also been shown to regulate nutrient ingestion and metabolism by altering the composition of gut microbiota and intestinal transport.…”
Section: Introductionmentioning
confidence: 99%